2019
DOI: 10.1001/jamaophthalmol.2019.0571
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of a Popular Online Symptom Checker for Ophthalmic Diagnoses

Abstract: IMPORTANCEBecause more patients are presenting with self-guided research of symptoms, it is important to assess the capabilities and limitations of these available health information tools.OBJECTIVE To determine the accuracy of the most popular online symptom checker for ophthalmic diagnoses. DESIGN, SETTING, AND PARTICIPANTSIn a cross-sectional study, 42 validated clinical vignettes of ophthalmic symptoms were generated and distilled to their core presenting symptoms. Cases were entered into WebMD symptom che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 12 publications
2
52
0
Order By: Relevance
“…This study has gone further than the Semigran study in that it has attempted to contextualise the risk averse behaviour that has previously been seen in this and other studies [9][10][11][12] .This study demonstrates that individuals are being recommended to access services that their symptoms do not warrant by many of the symptom checkers assessed, potentially putting additional pressure on resources and adding undue worry on individuals that they must seek medical care. Although perhaps not surprising given the increasingly litigious nature of healthcare on both sides of the Atlantic, this is a notable concern.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This study has gone further than the Semigran study in that it has attempted to contextualise the risk averse behaviour that has previously been seen in this and other studies [9][10][11][12] .This study demonstrates that individuals are being recommended to access services that their symptoms do not warrant by many of the symptom checkers assessed, potentially putting additional pressure on resources and adding undue worry on individuals that they must seek medical care. Although perhaps not surprising given the increasingly litigious nature of healthcare on both sides of the Atlantic, this is a notable concern.…”
Section: Discussionmentioning
confidence: 86%
“…Several previous studies 6-7 into the effectiveness of algorithmic performance have found deficiencies in the diagnostic capabilities and a cautious approach to triage. However, only one in 2015 (Semigran et al 8 ) examined multiple presentations and conditions; the others focussed on single condition studies such as those examining system performance for cervical myelopathy, inflammatory arthritis, HIV / Hepatitis C and ophthalmic conditions 9-12 . Given the refinement of existing models and the new entrants into the market since the 2015 study, the current clinical performance of these systems remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for lower Mediktor performance in the current study compared with the study in Moreno Barriga et al 7 is not known but it may be related to a different range of conditions or difficulty level than the non-urgent emergency cases presenting to the ED—for example—the vignettes in this study contain many true emergency cases and also many GP or pharmacy/treat-at-home cases which would not be represented by the ED patients included in Moreno Barriga et al 7 . In 2017, a 42-vignette evaluation of WebMD 28 determined its accuracy for ophthalmic condition suggestion: M1 was 26.0% and M3 was 38.0%. Urgency advice based on the top diagnosis was appropriate in 39.0% of emergency cases and 88.0% of non-emergency cases.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for lower Mediktor performance in the current study compared to [7] is not known but it may be related to a different range of conditions or difficulty level than the non-urgent emergency cases presenting to the ED - for example - the vignettes in this study contain many true emergency cases and also many GP or pharmacy/treat-at-home cases which would not be represented by the ED patients included in [7]. In a 2017 42-vignette evaluation of WebMD, [28] determined its accuracy for ophthalmic condition suggestion: M1 was 26.0% and M3 was 38.0%. Urgency advice based on the top diagnosis was appropriate in 39.0% of emergency cases and 88.0% non-emergency cases.…”
Section: Discussionmentioning
confidence: 99%